DR3 and its ligands take roles in periodontium remodeling during orthodontic tooth movement - Chuanliang Ling; Ruolin Cai; Yiming Gong; Xiaojun Ding (Elsevier, 2021)
Background/purpose: Based on 'pressure-tension theory', the application of orthodontic force to the tooth site affects the remodeling of periodontal tissue, specifically, mechanical stress induces the release of cytokines. The purpose of this research paper is to examine death receptor 3/TNF-like protein 1A/progranulin (DR3/TL1A/PGRN) expression levels in periodontium tissue during orthodontic tooth movement in rats. Materials and methods: Thirty-six ten-week-old male SD rats were used in this study. A total of 20 cN of orthodontic force was exerted by coil springs onto the upper right first molars in order for mesialization purposes. All rat members of their corresponding groups were euthanized based on the following time intervals: 0 day for the control group, 1 day (group two), 3 days (group three), 5 days (group four), 7 days (group five), and lastly 14 days for group six. The effects of DR3/TL1A/PGRN were observed through the use of immunohistochemical staining techniques. One-way analysis of variance followed by a LSD t-test was performed by SPSS 20 to compare the differences of the level of DR3/TL1A/PGRN amongst each specified time interval. Results: The expression levels of DR3/PGRN increased significantly on day 14 compared to that of the control group, thus indicating a wide range of statistical differences. The expression levels of TL1A soared upwards on day 1, then plunged to an all-time low on day 7 before finally bouncing back to its initial value on day14. Conclusion: DR3 and its two ligands-PGRN and TL1A play indispensable roles in regulating periodontal ligament remodeling during orthodontic tooth movement.